Prevalence and risk factors of depression among community dwelling elderly - Yaka, Erdem; Keskinoğlu, Pembe; Uçku, Reyhan; Yener, Görsev; Tunca, Zeliha (Elsevier Ireland Ltd, Elsevier House, Brookvale Plaza, East Park Shannon, Co, Clare, 00000, Ireland, 2014)
Depression in the elderly is associated with increased morbidity and mortality. The purpose of this study was to determine the prevalence and risk factors of depression among community-dwelling older population in an urban setting in Turkey. This cross-sectional study was conducted among 482 elderly individuals 65 years and over in an urban area. Cluster sampling method was used for sample size. Depression in the elderly had been diagnosed by a clinical interview and Geriatric Depression Scale. Data were collected by door-to-door survey. Chi square test was used for statistical analysis. P value, which was calculated by the results of chi square test and coefficient of phi (phi) below 0.05 was included in the analysis of logistic regression. Depression was significantly associated with female gender, being single or divorced, lower educational status, low income, unemployment, and lack of health insurance. However, logistic regression analysis revealed higher depression rates in the elderly with chronic obstructive pulmonary disease, psychiatric disease, cerebrovascular disease, low income and being dependent. Depression is common among community-dwelling older people in an urban area of Izmir, Turkey. Older adults living in community should be cautiously screened to prevent or manage depression. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Depression; Prevalence; Risk factor; Older adult; Turkey; Older-Adults; Care; People; Population; Predictors; Symptoms; Dementia; Sample; Model